Pollution of coals of the Upper Silesian Coal Basin from the perspective of the European registers of the release and transfer of pollutants to air - the case of chlorine. (July 2018) - Pluta, Szymon; Plewa, Franciszek
Abstract: The regulation WE 166 (2006) of the European Parliament and European Council on the establishment of the European Register of Release and Transfer of Pollutants presents the limiting values of pollutants to the atmosphere and values from mining operations and power plants. Chlorine and its compounds constitutes a significant pollutant. Taking into account the chlorine content of selected coals (up to 2.69% in the ashes) and the limiting values of the releases into the atmosphere one should perform a detailed analysis of its release from coal mines and power plants to the environment.